"CULTURAL CHRISTIANS" AND THE SEARCH FOR CIVIL SOCIETY IN CONTEMPORARY CHINA. (1st May 2013) - Xi, Lian
Abstract : This article traces the emergence of political and legal activism among China's Protestant elites since the turn of the twenty-first century. It explores the work and the writings of several contemporary public intellectuals and activists who have discovered in their newfound Protestant faith a sacred ground upon which they stand in opposition to the arbitrary powers of the Party-state. Other liberals such as Liu Xiaobo also see Christianity as offering guidance for both democratization and moral regeneration of Chinese society—a theme that echoes many Chinese intellectuals' response to Christianity at the birth of the Republic a century earlier.